MCMC for inference on phase-type and masked system lifetime models - Aslett, Louis J.M. (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2012)
Common reliability data consist of lifetimes (of censoring information) on all components and systems under examination. However, masked system lifetime data represents an important class of problems where the information available for statistical analysis is more limited: one only has failure times for the system as a whole, but no data on the component lifetimes directly, or even which components had failed. For example, such data can arise when system autopsy is impractical or cost prohibitive.
Keywords: Computer Science & Statistics, Ph.D.; Ph.D. Trinity College Dublin